Venous Thromboembolism: Genetics and Thrombophilias - Gaddh, Manila; Rosovsky, Rachel P. (Seminars in Respiratory and Critical Care Medicine, 2021)
Venous thromboembolism (VTE) is a major cause of morbidity and mortality throughout the world. Up to one half of patients who present with VTE will have an underlying thrombophilic defect. This knowledge has led to a widespread practice of testing for such defects in patients who develop VTE. However, identifying a hereditary thrombophilia by itself does not necessarily change outcomes or dictate therapy. Furthermore, family history of VTE by itself can increase an asymptomatic person's VTE risk several-fold, independent of detecting a known inherited thrombophilia. In this article, we will describe the current validated hereditary thrombophilias including their history, prevalence, and association with VTE. With a focus on evaluating both risks and benefits of testing, we will also explore the controversies of why, who, and when to test as well as discuss contemporary societal guidelines. Lastly, we will share how these tests have been integrated into clinical practice and how to best utilize them in the future.
Keywords: thrombophilia; venous thromboembolism; pulmonary embolism; deep vein thrombosis; hereditary